An Optimal Distillation Process for Turpentine Separation Using a Firefly Algorithm - Gustavo Mendes Platt; Otávio Knevitz de Azevedo; Francisco Bruno Souza Oliveira (Modelling, 2025)
The optimal design of distillation separation processes has become a fundamental tool in industries in order to minimize operating costs and investments. In many cases, the optimization stage has been carried out using metaheuristics, with the process simulation stage carried out externally to the optimization. This paper presents an optimal design methodology for separating the components of turpentine, a raw material of natural origin, based on coupling a distillation process simulator with the Firefly metaheuristic as an optimizer. Results were obtained for a distillation process to obtain <semantics>α</semantics>-pinene and <semantics>β</semantics>-pinene (two of the main components of turpentine), meeting purity criteria in the top products of the equipment while minimizing a measure of the total annualized cost. The results show that the tool developed—together with the Firefly algorithm—is capable of obtaining optimized results (although there is no guarantee of a global optimum) from a small set of initial design configurations.